Efektivitas Program Perluasan Sawah Dalam Peningkatan Produksi Padi di Distrik Tanah Miring Kabupaten Merauke - Erma Adriana Elsoin (AGRICOLA, 2019)
The Program Of Expansion Rice Fields On Rice Production In Current District Tanah Miring Regency Of Merauke. This research aimed to analyze the effectiveness the rice field expansion program in increasing paddy production. The research was conducted using descriptive quantitative approach. The research location was Tanah Miring Sub-District, Merauke Regency. The data collection was done using structural interviews through the questionnaires and the written documents. The 88 samples were chosen using Slovin formula and the sampling probability approach. The data were analyzedusing descriptive quantitative approach. The research results indicated that the farmers evaluation in relation to the effe ctiveness of the rice field expansion program in increasing the paddy production in Tanah Miring Sub-District, Merauke Regency were categorized as effective and effective enough.